2010
DOI: 10.3109/02841851.2010.520024
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided detection system applied to full-field digital mammograms

Abstract: CAD with FFDM showed a high sensitivity in identifying cancers manifesting as calcifications or masses. CAD sensitivity was maintained in small lesions (1-20 mm) and invasive lobular carcinomas, which have lower mammographic sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
3
10
1
Order By: Relevance
“…Single reading with CAD was found to have comparable cancer detection rates to double reading by radiologists but with a slight increase in recall rates 7 . One study demonstrated that CAD improved radiologist sensitivity by 21% in digitised mammograms 8 whereas other researchers found that CAD with FFDM showed a high sensitivity in detecting cancers manifesting as calcifications or masses and that CAD sensitivity was maintained in small lesions of 1 to 20mm and invasive lobular carcinoma 9,10 . Single reading with CAD is used routinely in a number of countries, notably in the United States.…”
Section: Introductionmentioning
confidence: 97%
“…Single reading with CAD was found to have comparable cancer detection rates to double reading by radiologists but with a slight increase in recall rates 7 . One study demonstrated that CAD improved radiologist sensitivity by 21% in digitised mammograms 8 whereas other researchers found that CAD with FFDM showed a high sensitivity in detecting cancers manifesting as calcifications or masses and that CAD sensitivity was maintained in small lesions of 1 to 20mm and invasive lobular carcinoma 9,10 . Single reading with CAD is used routinely in a number of countries, notably in the United States.…”
Section: Introductionmentioning
confidence: 97%
“…Mammographic breast density is one of of the significant risk factors for breast cancer [2]. In addition, sensitivity of breast cancer detection is reduced when reading mammograms of denser breasts for both radiologists [3] and Computer Aided Systems (CADs) [4]. Therefore, different methods, either qualitative or quantitative, have been proposed for measuring breast density.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed that CAD can reduce the false negative rate and increase the detection of breast cancer, particularly early breast cancer [2,3,8-10] without a significant increase in recall rate [2,8] and false positive rate for biopsy [8,10]. More recent studies have reported that CAD systems for full-field digital mammograms can also improve the diagnostic performance of mammograms [11,12]. Yang et al reported that the CAD system can correctly mark most asymptomatic breast cancers detected with digital mammographic screening [11], and Bolivar et al demonstrated that improved CAD sensitivity was maintained for small lesions and invasive lobular carcinomas, which have lower mammographic sensitivity [12].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have reported that CAD systems for full-field digital mammograms can also improve the diagnostic performance of mammograms [11,12]. Yang et al reported that the CAD system can correctly mark most asymptomatic breast cancers detected with digital mammographic screening [11], and Bolivar et al demonstrated that improved CAD sensitivity was maintained for small lesions and invasive lobular carcinomas, which have lower mammographic sensitivity [12]. …”
Section: Introductionmentioning
confidence: 99%